Estudio de factibilidad para la creación de una empresa dedicada a la producción y comercialización de abrigos impermeables para damas en la ciudad de Quito - Ortega Riofrío, Nathaly Fernanda (2013)
The objective of this feasibility project is to provide to Quito market any option to be safe of the low temperatures of winter without losing the elegance that characterizes the ladies in Quito City. The product of this research is a raincoat that is made with a waterproof material that avoids that the water penetrating the fabric, one of the most important benefits about this product is that it has wonderful designed. During the development of this research the main objective was determining the financial, economic and social benefits to create a company dedicated to the production and selling of waterproof coats or called also as raincoat for ladies in the capital of Ecuador. This research is divided into several interested chapters listed below: